PENGEMBANGAN MEDIA SPHERE AR PADA MATERI RELIEF BUMI KELAS V DI SEKOLAH DASAR - Hana Fitriani; Atep Sujana; Cucun Sunaengsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a learning media called Sphere AR based on Augmented Reality (AR) for the topic of Earth’s surface relief, which includes the lithosphere and hydrosphere, in the IPAS subject for fifth-grade elementary school students. The background of this research lies in the limited use of technology-based learning media that can help visualize the abstract concepts of Earth’s surface relief. Sphere AR is designed to provide a more interactive experience for students through the integration of AR technology. This study uses the Research and Development (R&D) method with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection techniques include interviews, expert validation, and student response questionnaires. The results of the study indicate that Sphere AR is deemed suitable for use in learning and received positive responses from students. Therefore, Sphere AR can contribute to improving the quality of IPAS learning, particularly in helping students understand the concept of Earth’s surface relief in a more engaging and interactive way.